Ortho- and meta-tyrosine formation from phenylalanine in human saliva as a marker of hydroxyl radical generation during betel quid chewing - Nair, Urmila; Nair, Jagadeesan; Friesen, Marlin D.; Bartsch, Helmut; Ohshima, Hiroshi (Carcinogenesis, 1995)
The habit of betel quid chewing, common in South-East Asia and the South Pacific islands, is causally associated with an increased risk of oral cancer. Reactive oxygen species formed from polyphenolic betel quid ingredients and lime at alkaline pH have been implicated as the agents responsible for DNA and tissue damage. To determine whether hydroxyl radical (HO) is generated in the human oral cavity during chewing of betel quid, the formation of o- and m-tyrosine from L-phenylalanine was measured, Both o- and m-tyrosine were formed in vitro in the presence of extracts of areca nut and/or catechu, transition metal ions such as Cu2+ and Fe2+ and lime or sodium carbonate (alkaline pH). Omission of any of these ingredients from the reaction mixture significantly reduced the yield of tyrosines. Hydroxyl radical scavengers such as ethanol, D-mannitol and dimethylsulfoxide inhibited the phenylalanine oxidation in a dose-dependent fashion. Five volunteers chewed betel quid consisting of betel leaf, areca nut, catechu and slaked lime (without tobacco). Their saliva, collected after chewing betel quid, contained high concentrations of p-tyrosine, but no appreciable amounts of o- or m-tyrosine. Saliva samples from the same subjects after chewing betel quid to which 20 mg phenylalanine had been added contained o- and m-tyrosine at concentrations ranging from 1010 to 3000 nM and from 1110 to 3140 nM respectively. These levels were significantly higher (P< 0.005) than those of subjects who kept phenylalanine in the oral cavity without betel quid, which ranged from 14 to 70 nM for o-tyrosine and from 10 to 35 nM for m-tyrosine. These studies clearly demonstrate that the HO radical is formed in the human oral cavity during betel quid chewing and is probably implicated in the genetic damage that has been observed in oral epithelial cells of chewers.
Gesehen am 11.01.2024